A Syntax of Substance - Adger, David (Book collections on Project MUSE., 2013)
The author proposes a new approach to phrase structure that eschews functional heads and labels structures exocentrically. The proposal simultaneously simplifies the syntactic system and restricts the range of possible structures, ruling out the ubiquitous (remnant) roll-up derivations and forcing a separation of arguments from their apparent heads. This new system has a number of empirical consequences, which the book explores in the domain of relational nominals across different language families, including Germanic, Romance, Celtic, Polynesian, and Semitic.